2013
DOI: 10.1158/0008-5472.sabcs13-p6-04-14
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P6-04-14: mRNA expressions of lamin B1 and lamin B receptor: Clinical correlations with human breast cancer

Abstract: BACKGROUND: Lamin B (LMNB) and lamin B receptor (LBR) are key components of the nuclear envelope, with roles in chromosomal stability, DNA repair, and cell differentiation. Lamins provide structural support to the nuclear envelope, while LBR is believed to anchor lamin B to the envelope. In addition, LBR also has a number of downstream mediators which affect cell cycle and cell differentiation. Classically, they have been implicated in a spectrum of largely congenital ailments including certain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Finally, several previous studies reported that the expression of senescence biomarkers correlated with poor outcomes in different kinds of cancers such as breast, colon, and bone cancer [ 35 , 71–73 ]. In addition to determining the extent of senescence induction in vivo , the exact role of senescence in determining the outcome of therapy is still debatable [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several previous studies reported that the expression of senescence biomarkers correlated with poor outcomes in different kinds of cancers such as breast, colon, and bone cancer [ 35 , 71–73 ]. In addition to determining the extent of senescence induction in vivo , the exact role of senescence in determining the outcome of therapy is still debatable [ 74 ].…”
Section: Discussionmentioning
confidence: 99%